Screening of chitinolytic activities of Geomyces spp. isolated from Fildes Peninsula, King George Island, Antarctica / Fawzyah Obeedallah Albaldi - Albaldi, Fawzyah Obeedallah (2012)
The first part in this research, was screened six strains of Geomyces spp. isolated from King George Island in the Maritime Antarctica for chitinase enzyme. Initially, microfungi were grown at 4 °C and 25 °C on a series of plates each containing 1% colloid chitin, 0.5% (NH4)2SO4, 0.05% MgSO4.7H2O, 0.24% KH2PO4, 0.06% K2HPO4.3H2O and 1.5% agar. Colony radius and hydrolytic activity were measured and a relative activity index (RA) constructed. Relative activity values at 25 ˚C were higher than at 4 ˚C. Only Geomyces sp. 5 (AKA7KGI102 R1-4) showed significant chitinase activity at both temperatures. Obviously, effective hydrolysis occurred at mesophilic temperatures. Second part, is quantification of enzyme by growing the selected strains on liquid medium at 25 ˚C. The selected strains were Geomyces sp. 1 (AKA7KGI601 R3-1) and Geomyces sp. 5 (AKA7KGI102 R1-4). Shake flask culture was carried out to produce chitinase enzyme using colloid chitin as the reference substrate. It was observed that protein concentration and N-acetylglucosamine production from Geomyces sp. 5 (AKA7KGI102 R1-4) was higher than from Geomyces sp. 1 (AKA7KGI601 R3-1). Optimization of culture medium was conducted in order to enhance enzyme activity. Medium with pH 6.5 exhibited the optimum chitinase activity and incubation temperature at 37 ˚C increase chitinase activity. However, potential Geomyces spp. have a great interest for used in future research. For its ability to produce chitinase at different temperatures it could be valuable in various biotechnological application.